The Social and Economic Situations of The City of TripoH in The Middle of The Seventeenth Century (According to The Tahrir Defteri Dated 1645) - Çakar, Enver (Ankara Üniversitesi, 2004)
This study examines the quarters and the populatin of the city of Tripali in the middle of the seventeenth century, according to the tahrir defteri (the tax register). Tripali had 26 quarters (mahalla) and its population was about 12- 17.000 at that time. The most of the urban population were Muslims. But, alsa there were Christians and Jews in this city. The port of Tripali was very important for the economy of the city. The other side, the productions of olive and mulberry had important place in the economy. And in relatian to this development, the productions of silk and soap had alsa important development as side productions

Bu çalışmada, 1645 tarihli mufassal tahrir defterinde yer alan bilgilerin ışığıııda, Akdeniz'in doğu sahilinde yer alan Trablusşam şehrinin mahalleleri, nüfusu ve nüfusun etnik ve dinı yapısı ile şehrin iktisadı durumu tespit edilmeye çalışılmıştır. Söz konusu deftere göre, XVII. YÜZyılııı ortalarında Trablusşam 'lll 26 mahallesi vardı, 12-17 bin civarında olan şehir nüfusunun çoğunluğunu Müslümanlar meydana getirmekle birlikte, Hıristiyanların da sayısı şehir nüfusuna oranla bir hayli fazlaydl. Ayrıca, şehirde az sayıda Yahudi de yerleşmişti. Trablusşam 'ın ekonomisinde en önemli yeri iskele gelirleri teşkil ediyordu. Diğer taraftan, zeytin ve dut yetiştiriciliğinde önemli bir mevkie sahip olan Trablusşam 'ııı, bunlara bağlı olarak, ipekçilik ve sabun üretiminde de hatırı sayılır bir ilerleme kaydettiği görülmektedir
XVII. YUZYILIN ORTALARıNDA TRABLUSŞAM ŞEHRİNİN SOSYAL VE İKTİsADI DURUMU (1645 Tarihli Mufassal Tahrir Defterine Göre)
Keywords: Archaeology; Arkeoloji